EFFECTIVENESS AND EFFICIENCY OF WEED CONTROL ON IMATURE PLANTS (TBM) II AT PT. SOCFINDO KEBUN SEUANGAN AFDILLING 1 - Nadiatul Asra; Teuku Athaillah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
There are so many problems found in the process of maintaining and increasing the production of oil palm plants. That is the benchmark for the success or failure of these plants. So far weeds are one of the most important problems because weeds interfere with the main crops during their growth and development.Many problems and losses are caused by the presence of weeds in an area if allowed to grow uncontrollably. Therefore, so that these weeds do not cause more serious problems, it is necessary to control weeds. This research is carried out. Every research is expected to be useful for all parties who read it and those who are directly involved in it.This study aims to determine the Effectiveness and Efficiency of weed control on immature plants both manually and chemically as seen from the comparison of control time, cost analysis, work performance, weed mortality rate and regrowth rate from manual and chemical weed control. The method used in this study is to use descriptive analysis method. FromThe results of this study indicate that chemical weed control is more effective and manual weed control is more efficient.